2006
DOI: 10.1021/ac061261f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen/Deuterium Scrambling during Quadrupole Time-of-Flight MS/MS Analysis of a Zinc-Binding Protein Domain

Abstract: It remains an open question as to whether experiments involving collision-induced dissociation (CID) can provide a viable approach for monitoring spatially resolved deuteration levels in electrosprayed polypeptide ions. A number of laboratories reported the successful application of CID following solution-phase H/D exchange (HDX), whereas others found that H/D scrambling precluded site-specific measurements. The aim of the current work is to help clarify the general feasibility of HDX-CID methods, using a 22-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 54 publications
7
99
1
Order By: Relevance
“…Bovine cyt c contains a total of 192 exchangeable hydrogens [53]. Hydrogen back exchange in the gas phase is negligible under the conditions used here [64].…”
Section: Mass Spectrometry Liquid Chromatography (Lc)/ Ms and Hydromentioning
confidence: 95%
See 1 more Smart Citation
“…Bovine cyt c contains a total of 192 exchangeable hydrogens [53]. Hydrogen back exchange in the gas phase is negligible under the conditions used here [64].…”
Section: Mass Spectrometry Liquid Chromatography (Lc)/ Ms and Hydromentioning
confidence: 95%
“…The mass distribution of a broadened peak p after HDX may be approximated as a convolution of the protein's shifted mass profile f with a Gaussian distribution function D [64]. This can be expressed as…”
Section: Hydrogen/deuterium Exchangementioning
confidence: 99%
“…In comparison, deprotonated peptides have received much less attention, and the mechanistic details of their fragmentation behavior are less well understood. We and others have previously investigated the proton mobility in protonated peptides and proteins upon collision-induced dissociation (CID) [2][3][4][5][6][7][8][9][10][11][12]. Our studies were motivated by earlier reports claiming that CID could be used to determine site-specific incorporation of deuterium in the backbone amides of peptides that were deuterated in solution [13][14][15][16].…”
mentioning
confidence: 99%
“…Our data showed that the deuteration level of Cterminal fraction (short z . ions) is higher than that of the Nterminal fraction (short c ions) after 24 h full H/D exchange, which is attributed that C-terminal fraction contains a highly flexible tail (residues 71-76) and N-terminal fraction contains two hydrogen-bonded β-strands (residues 1-7 and residues 10-17) and a tightly packed α-helix (residues [23][24][25][26][27][28][29][30][31][32][33][34]. The α-helix region showed the lowest deuteration level, and the turn (residues 8-11) on the surface of the protein that connects two adjacent β-strands showed very high deuteration level.…”
Section: Discussionmentioning
confidence: 94%
“…[20][21][22][23][24][25] However, others showed apparent scrambling resulted from CID in HDX/MS/MS studies. [26][27][28][29] Even though it has been reported that another threshold dissociation method, infrared multiphoton dissociation (IRMPD), 30,31 causes little or no deuterium scrambling in HDX-MS, 32 the labile modifications are lost prior to backbone cleavage, thus making it difficult to identify the modification site. Recently, Polfer and co-workers have reported abundant NH 3 and H 2 O losses from b fragments when employing IRMPD in HDX studies and they also reported that SORI CID (sustained offresonance irradiation collision-induced dissociation) 33 can cause more scrambling products and internal fragments.…”
mentioning
confidence: 99%